Evaluasi Prosedur Pemberian Kredit Cepat Aman (KCA) dan Kredit Angsuran Sistem Fidusia (KREASI) pada PT. Pegadaian (PERSERO) Cabang Ende - Koten, Anselmus Jemadi; Thalib, Sabra B Wahab; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2021)
This study aims to determine the procedure for granting credit Fast and Amana (KCA) and Fiduciary System Installment Credit (KREASI) at PT. Pegadaian (Persero) Ende Branch. This type of research used in this research is descriptive research. The method used in this study is a qualitative descriptive method that seeks to describe a phenomenon, event, event that occurred. Descriptive research focuses on the actual problem as it was when the research took place. Sources of data used in this study are primary data and secondary data, while data collection techniques are done by observation, interviews, and documentation. The results of research conducted at PT. Pegadaian (Persero) Ende Branch regarding Evaluation of KCA and KREASI credit granting procedures, shows that the procedure for granting credit to PT. The Ende Branch Pawnshop has been implemented well in accordance with existing theories, but there is a need for improvement in several related functions and improvements such as the appraisal function is separated from the storage section and the cashier function is separated from the administrative function so that the credit granting process can run well.